Problematising the notion of 'the excellent teacher': daring to be vulnerable in higher education. Issue 2 (17th February 2023) - Mangione, Daniela; Norton, Lin
ABSTRACT: The paper puts forward the case for vulnerability as an important element within higher education pedagogy. In a context of rapid change and competing demands in the global higher education sector, the zeitgeist is that of teaching excellence, usually measured by a market-driven metrics approach. Teachers might, therefore, feel pressured not to reveal weaknesses either to their students or to their colleagues, and might tend to position themselves far away from any kind of vulnerability mode. Pedagogic vulnerability is a complex concept, liable to diverse interpretations and definitions. In an attempt to understand it more clearly, different views are explored in the literature, combined with a reflective analysis of two autoethnographic narratives portraying examples of vulnerability in teaching. This examination generated five principles of pedagogic vulnerability which are suggested as an approach to rethinking the purpose of higher education and the notion of teaching excellence.